1997
DOI: 10.1038/sj.bjp.0701233
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of the neuropeptide galanin on striatal acetylcholine release in anaesthetized and awake rats

Abstract: 1 In the present study the mechanisms were examined by which the neuropeptide galanin modulates the extracellular concentrations of striatal acetylcholine (ACh) in en¯urane anaesthetized and in freely moving male rats by use of in vivo microdialysis and high performance liquid chromatography. 2 The perfusion of galanin through the microdialysis probe (0.3 nmol ml 71 ,¯ow rate: 2 ml min 71 ) caused a statistically signi®cant increase in the basal striatal ACh levels in anaesthetized but a decrease in awake anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…Since, M35 has about the same affinity for both GalR1 (Ki ϭ 0.3 nM) and GalR2 (Ki ϭ 0.6 nM) receptor subtypes, it is not possible to link the blockade of the galanin effect to any specific galanin receptor subtype in the DRN. Administration of M35 itself caused a slight but significant reduction of basal extracellular 5-HT at 120 min, which is in agreement both with in vitro data in insulinoma cell lines (Kask et al 1995) and in vivo data showing a partial agonistic mode of action of M35 (Antoniou et al 1997). The temporal increase of the 5-HT levels at 20-40 min following galanin administration in the M35 pretreated group could be explained by an increased sensitivity to the acute stress caused during the insertion of the i.c.v.…”
Section: Discussionsupporting
confidence: 90%
“…Since, M35 has about the same affinity for both GalR1 (Ki ϭ 0.3 nM) and GalR2 (Ki ϭ 0.6 nM) receptor subtypes, it is not possible to link the blockade of the galanin effect to any specific galanin receptor subtype in the DRN. Administration of M35 itself caused a slight but significant reduction of basal extracellular 5-HT at 120 min, which is in agreement both with in vitro data in insulinoma cell lines (Kask et al 1995) and in vivo data showing a partial agonistic mode of action of M35 (Antoniou et al 1997). The temporal increase of the 5-HT levels at 20-40 min following galanin administration in the M35 pretreated group could be explained by an increased sensitivity to the acute stress caused during the insertion of the i.c.v.…”
Section: Discussionsupporting
confidence: 90%
“…The interval between the s.c. administration of scopolamine and training in this study was 40 min, which is longer than in most previous PA studies (varying usually between 5 and 30 min) (Bammer, 1982). The choice of this time interval was based on in vivo microdialysis studies, in which s.c. scopolamine produced an increase in the ACh levels in the ventral hippocampus with a peak effect after 40-60 min (Antoniou et al, 1997;Ö gren et al, 1996;Toide and Arima, 1989).…”
Section: Discussionmentioning
confidence: 93%
“…Whereas mRNA levels for galanin receptors are low in the NAc, galanin receptor binding is quite prominent (Burgevin et al, 1995;Gustafson et al, 1996;Hawes and Picciotto, 2004;Kolakowski et al, 1998;Waters and Krause, 2000), indicating that localization of galanin receptors on DA terminals might regulate DA release. Galanin is also known to be a potent inhibitory modulator of basal acetylcholine (ACh) release in the striatum (Antoniou et al, 1997) and it has been demonstrated that M1-muscarinic receptors and high-affinity nicotinic receptors regulate the secondary rewarding effects of cues paired with a primary reinforcer such as morphine (Brunzell et al, 2006;Carrigan and Dykstra, 2007). Lack of galanin may therefore increase availability of ACh, thus increasing the sensitivity of GKO mice to opiates.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of galanin may therefore increase availability of ACh, thus increasing the sensitivity of GKO mice to opiates. Finally, galanin has also been shown to decrease GABA release in the cortex and striatum (Antoniou et al, 1997;Ellis and Davies, 1994), potentially increasing excitability in these brain areas and contributing to morphine's behavioral effects. The effects of galanin on morphine-related behaviors may therefore modulate reward pathways through multiple neurotransmitter systems.…”
Section: Discussionmentioning
confidence: 99%